A Framework for Analysing Disinformation Narratives: Ukrainian Refugees in Bulgaria - Kiely Keith Peter; Gargova Silvia (Cybernetics and Information Technologies, 2024)
This article presents a methodological framework for analyzing disinformation narratives, emphasizing the significance of localized contextualization, particularly the influence of cultural and historical factors embedded within these narratives. Understanding these elements is crucial for unpacking the dynamics and power relations present in disinformation discourses. The study focuses on misleading information regarding Ukrainian refugees in Bulgaria, a country vulnerable to disinformation yet often overlooked in research, partly due to its linguistic context. Additionally, the paper advocates for the application of Gramscian theories of hegemony and the “war of position” as contextual lenses to enhance the theoretical and methodological framework. This framework employs a discourse analysis approach, supplemented by Natural Language Processing (NLP), enabling the capture of critical aspects of disinformation dynamics and yielding multi-layered, informative, and actionable insights.